2014
DOI: 10.1002/mabi.201300443
|View full text |Cite
|
Sign up to set email alerts
|

Additive Benefits of Chondroitin Sulfate and Oriented Tethered Epidermal Growth Factor for Vascular Smooth Muscle Cell Survival

Abstract: An anti-apoptotic coating combining chondroitin sulfate (CS) and coiled-coil-based tethering of epidermal growth factor (EGF) is designed for vascular applications. The oriented tethering strategy enables to reach higher EGF surface densities compared to the commonly used random covalent grafting, while using much lower concentrations of EGF during incubation. It also significantly improves vascular smooth muscle cell (VSMC) survival and resistance to apoptosis in serum-free conditions. The comparison of CS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…As opposed to HUVEC, E-VEGF immobilization alone showed little enhancement of AoSMC survival (31 ± 5 % for surfaces incubated with E-VEGF at 20 nM compared to 20 ± 7 % for bare CS surfaces). However, as previously reported, the coiled-coil immobilization of E-EGF on CS led to a significant increase in cell survival, [37] and this pro-survival effect increased with the E-EGF incubation concentration (from 27 ± 12 % for 0.1-nM E-EGF to 53 ± 9 % for 20-nM E-EGF). Once again, a further increase in cell survival was observed for surfaces incubated with a mixture of GFs.…”
Section: Aosmcsupporting
confidence: 80%
See 3 more Smart Citations
“…As opposed to HUVEC, E-VEGF immobilization alone showed little enhancement of AoSMC survival (31 ± 5 % for surfaces incubated with E-VEGF at 20 nM compared to 20 ± 7 % for bare CS surfaces). However, as previously reported, the coiled-coil immobilization of E-EGF on CS led to a significant increase in cell survival, [37] and this pro-survival effect increased with the E-EGF incubation concentration (from 27 ± 12 % for 0.1-nM E-EGF to 53 ± 9 % for 20-nM E-EGF). Once again, a further increase in cell survival was observed for surfaces incubated with a mixture of GFs.…”
Section: Aosmcsupporting
confidence: 80%
“…Indeed, in a previous study, we observed that the coiled-coil mediated EGF immobilization allowed higher capture efficiencies compared to covalent grafting. [37] Another explanation for the signal saturation we observed, especially in the case of E-VEGF, could be a saturation of the Kcoil units on CS, since the secondary capture of E-EGF on surfaces pre-incubated with E-VEGF at concentrations higher than 5 nM did not occur (Fig. 3).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This choice is based on previous studies that have shown the superiority of the combination of CS and EGF [14]. The coating was created on polyethylene terephtalate (PET) and expanded polytetrafluoroethylene (ePTFE) substrates (since these are the two plastic materials used in SG graft fabric) and tested in vitro for its bioactivity on vascular cells and its stability.…”
Section: Methodsmentioning
confidence: 99%